Suomalaisten arkeologien exlibriksiä - Taavitsainen Jussi-Pekka (Suomen arkeologinen seura, 2023)
The article presents the bookplates – decorative labels pasted into books to indicate ownership – of all Finnish archaeologists known to the author. It explores how their themes are linked/connected to the research and work history of the owners as well as how they were obtained/acquired. The article also highlights the role of bookplates in maintaining and strengthening Finnish-Estonian relationships during the Soviet occupation period of Estonia. Keywords: bookplate, history of archaeology, Finnish-Estonian relations. Avainsanat: exlibris, arkeologian historia, suomalais-virolaiset suhteet
Oodeja Mikalle : juhlakirja professori Mika Lavennolle hänen täyttäessään 60 vuotta = Odes to Mika : Festschrift for professor Mika Lavento on the occasion of his 60th birthday = Ody Mike : ûbilejnyj sbornik posvâŝennyj 60-letiû professora Miki Lavento